Sporadic Intradural Extramedullary Hemangioblastoma of Cauda Equina with Large Peritumoral Cyst—A Rare Presentation - Thippeswamy, Pushpa B.; Soundararajan, Dilip C. R.; Kanna, Ríshi M.; Kuna, Venkata S.; Rajasekaran, Shanmuganathan (Indian Journal of Radiology and Imaging, 2021)
Cauda equina intradural tumors commonly reported include ependymoma, schwannoma, neurofibroma, meningioma, and drop metastasis. Hemangioblastoma of the neural axis is a rare benign vascular tumor comprising only 1.6 to 6.4% of spinal tumors, and are usually associated with Von-Hippel Lindau disease. Sporadic intradural extramedullary hemangioblastoma involving cauda equina is very rare with only countable reports, and the presence of peritumoral cyst has been reported only once. We report one such case of hemangioblastoma with a large peritumoral cyst, which was diagnosed radiologically and confirmed by histopathology following surgical excision. Pertinent radiological characteristics, diagnostic clues, treatment, and surgical outcomes are discussed.
Keywords: cauda equina tumors; cystic lesion; hemangioblastoma; intradural tumors